The Effect of Talking Chips Towards Students’ Self-Assurance in Speaking Skill - Sudirman Sudirman; Tya Putri Rahmadani (Universitas Pendidikan Mandalika, 2020)
This research is aimed to find out whether Talking Chips has positive effect or not toward students’ self-assurance in speaking of the second grade students at SMAN 4 Mataram. The research was experimental research and the design used was Pre Experimental with one group without control group and used one group pre-test post-test design only. The population of the study was the second grade students of SMAN 4 Mataram which consisted of one class (19 students). One class was chosen by using accidental sampling technique and the result was XI IPS 1. In collecting the data pre-test and post-test were done. And then, the data analyzed by using SPSS. The result of data analysis showed that t-test was 3.457 and t-table was 2.109, it means that t-test was higher than t-table as the level of significance level 0,05. It can be concluded that teaching self-assurance in speaking skill at SMAN 4 Mataram using talking chips produce much greater change in the students’ self-assurance in speaking. On the other words, talking chips technique is effective in teaching self-assurance in speaking at SMAN 4 Mataram.